CONCENTRATIONS EN ÉLÉMENTS TRACES MÉTALLIQUES DANS LES SOLS IRRIGUÉS PAR LES EAUX USÉES VERSÉES DANS L’OUED MERZEG (CASABLANCA –MAROC) - F. Matech; F. Zaakour; K. Moustarhfer; Z. Chemsi; I. Benazzouz; N. Saber (European Scientific Journal, ESJ, 2014)
The Moroccan Areas semi-arid know for more than twenty years a remarkable water deficit which had a significant impact on yields practiced in rainfed crops. The farmers in these areas have resorted to use an untreated sewage outfalls sometimes versed in their land. Thus, in Casablanca, domestic and industrial wastewaters rejected from Berrechid province into the Merzeg River are used in irrigation. In this study two approaches were chosen to evaluate the influence of this wastewater on soil quality: agronomic and environmental. A sampling campaign conducted in October 2013 allowed us to make samples according to the soil surface horizon at three stations along the Merzeg River from upstream to downstream. The main agronomic results show that pH is near to neutrality, the organic matter rate increase from upstream to downstream (from 1.86 to 2.69%) and the rate of calcium carbonate detectable in the first stations. The electrical conductivity Values are higher particularly in the station 3 (4.32 ms) as compared with the other stations. The concentrations of trace metals arsenic (As), cadmium (Cd), copper (Cu) are higher compared with non-irrigated field by the Merzeg River waters with Cu concentration exceed the threshold set by WHO.